Readiness, knowledge, and attitudes of healthcare professionals in Jordan toward Monkeypox: a cross-sectional survey - Ahmad Z. Al Meslamani; Dania Abu-Naser; Rami H. Al-Rifai (Scientific Reports)
Abstract Healthcare professionals play a vital role in managing and containing disease outbreaks. This study evaluated the level of readiness, knowledge, and attitudes of healthcare professionals in Jordan towards Monkeypox (Mpox) disease and explored factors associated with poor level of readiness, poor level of knowledge, and negative attitude toward Mpox. A pre-validated cross-sectional survey was carried out on healthcare professionals (physicians, pharmacists and nurses) actively involved in patient care in Jordan from 15 July to 30 September 2024. After being pilot-tested on 30 healthcare professionals, the 48-item questionnaire, collected information on participant’s demographics, and readiness, knowledge, and attitudes towards Mpox. Multivariable logistic regression identified factors associated with poor readiness, poor knowledge, and negative attitude. A total of 1093 healthcare professionals participated in the survey, including 329 physicians (30.1%), 346 pharmacists (31.7%), and 418 nurses (38.2%). Among participants, 58.0% demonstrated high levels of readiness, and 53.9% showed high levels of knowledge regarding Mpox. However, one-third (33.6%) were unaware of the availability of an effective vaccine, and only 30.7% recognized the lack of an effective treatment for Mpox. Nurses had higher readiness scores (median: 5, IQR: 5) compared to physicians (median: 4, IQR: 6) and pharmacists (median: 4, IQR: 6), while physicians scored highest in knowledge (median: 8, IQR: 4), followed by nurses (median: 7, IQR: 4) and pharmacists (median: 5, IQR: 4). No prior pandemic response experience was positively associated with increased likelihood of poor Mpox readiness (AOR: 2.11, 95% CI: 1.60–2.78) and poor knowledge (AOR: 1.40, 95% CI: 1.08–1.81). Poor knowledge was also linked to relying on workshops as the main information source (AOR: 2.55, 95% CI: 1.50–4.32). Negative attitudes were associated with lack of prior response experience (AOR: 1.36, 95% CI: 1.04–1.77), not using digital health records (AOR: 1.56, 95% CI: 1.18–2.05), and depending on colleagues for information (AOR: 1.73, 95% CI: 1.00–3.00) while attending workshop was protective against having negative attitude (AOR: 0.32, 95% CI: 0.17–0.60). While over half of healthcare professionals in Jordan demonstrated high readiness and knowledge regarding Mpox, significant gaps remain, particularly in vaccine and treatment awareness. Nurses showed higher readiness, whereas physicians had better knowledge levels. Targeted training and improved information dissemination strategies are needed to enhance Mpox response capacity among healthcare professionals.